G168(P) Child protection in a low resource setting; experiences from Paediatric professionals in Kenya. (7th April 2014) - Candler, TP; Gannon, H; Wachira, J
Abstract : Aims: Child protection is a significant issue in global child health. Children in Kenya are protected from abuse by international (United Nations Convention of the Rights of the Child 1989) and national (Children's Act 2001) legal frameworks. The recognition of the importance of child protection training is not new. In the UK repeated inquiries into child abuse cases have highlighted the essential need and importance of training professionals who come into contact with children. There is limited knowledge of professional's attitudes, confidence and training from resource poor settings with regard to child protection. The aim of this study is to investigate attitudes, experiences and training provision of child protection amongst Kenyan Paediatric consultants and trainees. Methods: A ten question survey was sent to paediatric professionals working in Kenya via the Kenyan Paediatric Association. Results: 58 responses were received. Only 29% of professionals had received formal child protection training in the last 5 years with 48% not receiving any training in their postgraduate years. Those that did attend formal training reported it to be useful with a mean score of 7.18 out of 10. Comments from participants supported the need for more formal and comprehensive training. The table demonstrates the mean confidence of professionals in recognising the different types of child protection cases, with trainees scoring lower than consultants in most areas. 64% of respondents were aware of child protection procedures in their hospital, but only 22% were aware of National Kenyan guidance. Conclusion: This is the first study to look at child protection training and experiences of health professionals from a low resource setting. The responses suggest that widespread formal training is needed to empower professionals to effectively recognise and manage cases of child abuse in Kenya.